Long-term Study on the Statistical Properties of Uterine and Umbilical Arterial Resistance Indexes by Simple Doppler Velocimetry in Patients with Perinatal Prognosis Stratification: Part II - García González, Salvador (CIENCIA ergo-sum; Vol. 5 Núm. 2 (1998): CIENCIA ergo-sum (julio-octubre 1998), 2017)
Simple Doppler velocimetry is a non-invasive morpho-functional technique whit great impact as a diagnostic auxiliary means in Perinatal Medicine, that has led to the adoption of many functional indexes. One remaining question to be answered is to define wish the probable interaction between uterine and umbilical arterial resistance indexes during fetal life. The answer will explain the effect of risk factors and/or final changes induced by etiopathogenic agents. The hypothesis of this approach consist of  that the statistical variability of such indexes is related with de biological strategy to archieve cardiovascular adaptation during the perinatal period Hence, the goal of this study is to analyze the statistical variability for both uterine and umbilical arterial resistance indexes, from long-term observations in three patients with very different perinatal prognosis but with common final condition of a live newbom  In this report a new way of compute the total arterial uterine resistance index is presented, and how the Friedman-Anova rank test is utilized to search the probable statistical difference for the corresponding arterial resistance indexes among patients. Also, the nonlinear regression by exponential growth adjustment is used to describe the statistical variability of patients'data. The total results obtained in this project support the beneficial approach of a long-term observational study and reveal a characteristic profile followed by three patients with very different perinatal prognosis as seen by the variability of statistical properties.